To investigate the relationship between work-family conflict and job satisfaction among front-line employees in Banking Industry in Kuching - Lee Yee, Jing (Universiti Malaysia Sarawak, (UNIMAS), 2019)
This study aimed to investigate the relationship between work-family conflict and job satisfaction among front-line employees in banking industry in Kuching. The survey research method was used and 160 sets of questionnaires had been distributed to a sample of front-line employees at eight branches of banks in Kuching. However, there were only 113 sets of questionnaires were collected. The data was then analyzed by using Statistical Package for Social Sciences (SPSS) version 22.0. From the reliability and validity analysis, it was indicated that the instrument of this research was reliable and valid. Statistical analyses such as Pearson Correlation Coefficient and Multiple Regression Analysis were used. Analysis from Pearson Correlation Coefficient had shown that there was a significant relationship between work-family conflict such as time-based conflict, strain-based conflict and behaviorbased conflict and job satisfaction. Besides that, Multiple Regression Analysis indicated that behavior-based conflict was the dominant factor that influenced more on job satisfaction. The findings implied that human resources practitioners can identify the importance of understanding work-family conflict that affects employees' job satisfaction. Furthermore, future researchers were recommended to conduct similar study based on the other workfamily conflict that affects employees' job satisfaction.